Economic Interdependence and the International Implications of Supply-Side Policies. (IMF Working Papers; Working Paper, 1988)
This paper analyzes the implications of growing international economic integration for the conduct of structural policy. Section I points out that the internationalization of financial intermediation has raised the welfare costs associated with domestic distortions. The growing importance of structural policies in affecting domestic demand in a more integrated world economy is discussed in Section II. It is shown that domestic distortions reduce the effect of expansionary policy on the domestic economy. Section III examines the international transmission of unilateral structural policies. Section IV discusses the need for the international coordination of structural policies. Section V identifies structural areas in which international policy coordination is most urgent.